Marine Biodiversity of Coral Reef Fishes in Pieh Marine Recreational Park After Bleaching and Acanthaster Outbreaks - Risandi Dwirama Putra; Muhammad Abrar; Rikoh Manogar Siringoringo; Ni Wayan Purnamsari; Pradipta Agustina; MD Jayedul Islam (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research • After bleaching disturbance and Acanthaster planci outbreaks, herbivore fishes species were dominated in MRP Pieh • This explains the marine recreational activities in utilization zone MRP Pieh have no impact on reducing fish biomass • After disturbance in MRP Pieh shows the coral reef fishes still endurance on bleaching event, and Acanthaster planci outbreak after disturbance in MRP Pieh shows the coral reef fishes still endurance on bleaching event and Acanthaster planci outbreak. However, the composition of corallivorous has decreased but has been an increase in herbivorous and carnivorous fish populations